On The Algebraic Properties of 2-Cyclic Refined Neutrosophic Matrices and The Diagonalization Problem - Rama Asad Nadweh; Rozina Ali; Maretta Sarkis (Neutrosophic Sets and Systems, 2023)
The n-cyclic refined neutrosophic algebraic structures are very diverse and rich materials. In this paper, we study the elementary algebraic properties of 2-cyclic refined neutrosophic square matrices, where we find formulas for computing determinants, eigen values, and inverses. On the other hand, we solve the diagonalization problem of these matrices, where a complete algorithm to diagonlaize every diagonalizable 2-cyclic refined neutrosophic square matrix is obtained and illustrated by many related examples.